Can music reduce national prejudice? A test of a cross-cultural musical education programme. (September 2019) - Neto, Félix; Pinto, Maria da Conceição; Mullet, Etienne
This study examined the impact of a cross-cultural musical program on young Portuguese adolescents' national prejudice. Two-hundred and twenty-nine sixth-grade pupils who attended public schools in the area of Lisbon, Portugal, were first presented with two tasks measuring national prejudice: a trait attribution task comprising positive and negative personality traits, and an overall affective evaluation of in-group and out-group people. Half of the pupils were subsequently exposed, at school, to a six-month musical program that included Cape Verdean songs as well as Portuguese songs. The other half was exposed to the usual program, which comprised no songs from Cape Verde but included all the Portuguese songs. Measures of national prejudice taken at the end of the program showed that the impact of the program was specific. In the experimental group, prejudice towards Cape Verdean people was reduced whereas attitudes to other groups were not altered (Portuguese and Brazilian). In the control group no reduction for any group was observed. Measures taken three months later showed that the impact of the experimental program was enduring.